Cutting-Edge Innovations: ICG Fluoroscopy in Colorectal Cancer and Liver Tumors - Casteleins, William Augusto; Thanh, Bùi Minh; Nghĩa, Nguyễn Văn (Asian Pacific Journal of Cancer Care, 2025)
Indocyanine Green (ICG) fluorescence imaging has been revolutionizing the surgical management of colorectal cancer and liver metastases by providing a dynamic real-time visualization of tissue perfusion, lymphatic pathways, and tumor margins. This innovative technology has demonstrated significant benefits in colorectal surgeries by reducing anastomotic leakage rates, enhancing vascular assessment, and improving the safety of anastomoses, thereby decreasing postoperative morbidity. In liver surgery, ICG fluorescence enables precise identification of metastatic lesions, particularly small or deep-seated tumors, and aids in achieving R0 resections with better oncological outcomes. Moreover, its capacity to visualize the boundaries of tumors intraoperatively enhances surgical precision while minimizing unnecessary tissue resection. Despite these advantages, widespread adoption of ICG fluorescence imaging is hindered by the lack of standardized protocols and reliance on subjective interpretation of fluorescence signals. Future advancements, such as quantitative fluorescence analysis, integration with artificial intelligence, and robotic-assisted platforms, are expected to overcome these limitations and further enhance the utility of ICG in surgical oncology. As a minimally invasive, cost-effective, and versatile tool, fluorescence represents a paradigm shift in the approach to managing colorectal cancer and liver metastases, offering patients safer and more precise surgical interventions.